Evaluating the Effects of Young Areca catechu Seed Extract on FSH and Testosterone Levels in Male Rats: Insights into Natural Anti-Fertility Agents - Noviyanti, Noviyanti; Sugito, Sugito; Akmal, Muslim; Saidi, Nurdin (Malacca Pharmaceutics, 2026)
Male participation in contraception remains limited worldwide because few safe and acceptable male contraceptive options exist. Natural products are being explored as potential regulators of male reproductive hormones. Areca catechu (areca nut), traditionally used in Southeast Asia, contains phytochemicals that may influence reproductive function. This study evaluated the effects of the ethanolic extract of young A. catechu seeds on serum follicle-stimulating hormone (FSH) and testosterone levels in male Wistar rats. Twenty-five rats were randomly assigned to five groups (0, 20, 40, 60, and 80 mg/kgbody weight) and treated daily for 48 days. Serum FSH and testosterone were measured by ELISA and analyzed by one-way ANOVA with Duncan’s post-hoc test. Mean FSH and testosterone values varied across doses, with the 40 mg/kg group showing the highest means (10.001 ± 10.413 ng/mL and 2.196 ± 1.254 ng/mL, respectively), but no statistically significant differences were detected for either hormone (FSH p = 0.043; testosterone p = 0.425). The results provide preliminary, hypothesis-generating evidence that the extract may influence the hypothalamic–pituitary–gonadal axis; however, any role in male fertility regulation remains unproven. Larger studies including sperm-quality assessment, mechanistic analyses, and toxicological evaluation are required before considering potential applications in male reproductive health.